Evaluation of the factors that make eating of hospitalized elderly difficult - Deise Feijó Lima; Edison Luiz Devos Barlem; Silvana Sidney Costa Santos; Jamila Geri Tomaschewisk-Barlem; Aline Marcelino Ramos; Kerolayne Machado de Mattos (Rev Rene)
This study is aimed at evaluating the factors that hinder the eating of hospitalized elderly. It is a quantitative and cross-sectional research, made with 92 hospitalized elderly patients in two hospitals in southern Brazil, between January and September 2012. For data collection an instrument called Eating Assessment Scale for the Elderly Hospitalized was used. A factorial and descriptive data analysis was made. Four factors related to the difficulty of eating in hospitalized elderly were identified: environmental factors, food, health team and physiological factors. The environmental factors were highlighted as the most difficult concerning eating of the elderly. It is concluded that the identified factors can contribute to the development of strategies which are aimed at assuring that the eating of the elderly occurs effectively during the period of hospitalization.